Current status and future trends of monitoring technologies for food products traceability - Morais, Diogo (2019)
This study is within the activities of Project “PrunusPós - Optimization of processes for the storage, cold conservation, active and/or intelligent packaging and food quality traceability in post-harvested fruit products”, project n.º PDR2020-101-031695, Partnership n.º 87, initiative n.º 175, promoted by PDR 2020 and co-funded by FEADER within Portugal 2020.